Students' perceptions of digital decoding technique to improve reading comprehension in digital text - Erica Putri Amalia; R. Bunga Febriani; Iskhak Said (Universitas Galuh, 2026)
The structure of digital text is different from printed text, since special techniques or strategies are required to understand digital text. Many challenges are encountered in digital texts, such as multimedia interference or loss of focus. This study aims to determine the use of digital decoding techniques in improving students' comprehension of digital texts. This digital decoding technique is implemented through associations between word sounds, meanings, and reading contexts, and is reinforced by the creation of 5W1H-based infographics to help students organize information from the texts they read. This study uses a qualitative approach with a phenomenological design, involving eighth-grade students at SMPN 3 Cisaga as participants. The data was collected through structured observations supplemented by field notes, which were then analyzed using descriptive analysis plus calls to action that include solutions or suggestions. The results of the study showed an increase in students' reading comprehension after the application of this technique. Students became more active and independent in reading, and their dependence on translation tools was reduced. The use of 5W1H-based infographics helped students organize important information, thereby improving comprehension and retention of reading content. This study contributes to enrich effective teaching strategies in digital literacy strategies. Further research is recommended to be conducted over a wider scope and longer period of time.